Prevalence of Protozoan Pathogens Among Diarrheic Children Under 5 Years in Public Hospital of Ethiopia During the Global COVID 19 Pandemic - Tesfaye Gobena PhD; Dinaol Belina DVM; Tine Hald PhD; Sara M. Pires PhD (SAGE Publishing, 2024)
Acute childhood diarrhea is one of the leading causes of childhood morbidity and mortality in sub-Saharan African countries. Entamoeba histolytica and Giardia lamblia are the common cause of childhood diarrhea in the region. However, there are only few studies on protozoa causing diarrhea in sub-Saharan African countries. This study was conducted to investigate the relative prevalence and explore risk factors of E. histolytica and G. lamblia among diarrheic children of under 5 years in a public hospital of Ethiopia. A retrospective study was conducted among diarrheic children at Hiwot Fana hospital, Ethiopia. Records of all diarrheic children less than 5 years who had sought medical treatment in the hospital from September 1, 2020 to December 31, 2022 were included. Data were collected from 1257 medical records of the children using a structured data-collection format. Data were entered into an Excel sheet and exported into SPSS version 22 for data processing and analysis. Descriptive statistical tests, Chi-square, and logistic region analysis were applied to determine predictors of protozoa infections. Of the 1257 cases, 962 (76.5%) had watery diarrhea and the remaining 239 (19.0%) had dysentery. The combined prevalence of E. histolytica and G. lamblia among diarrheic children was 11.8% (95% CI: 9.6-13.4). As the age of children increased, the frequency of these two protozoan infections was significantly increased compared to children with other causes. There were more diarrhea cases during the summer season including those associated with E. histolytica and G. lamblia . This study revealed that 1 in 10 causes of diarhhea among young children in the study area was likely caused by E. histolytica and G. lamblia . These findings call for community-based safe water and food safety interventions in order to reduce childhood diarrhea caused by protozoan infections in resource-poor settings.